Complexes of land mollusks of various biotopes of the ugam and pskom mountain ranges - A. Pazilov; F. Gaibnazarova; Z. Mukhammadiev (International Journal on Human-Computing Studies, 2021)
High numbers, wide distribution, large species diversity, low mobility and low ability to overcome geographical barriers, ease of material collection and sensitive response to changes in the environment make a group of land mollusks a convenient object of biogeographically and ecological research.